Birth by cesarean delivery and central adiposity in adolescents from a birth cohort - Joana D'Arc Matos França de Abreu; Sterffeson Lamare Lucena de Abreu; Maylla Luanna Barbosa Martins Bragança; Lilian Fernanda Pereira Cavalcante; Ana Karina Teixeira da Cunha França; Cecília Claudia Costa Ribeiro; Fernando Lamy Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: The aim of this study was to analyze the association between birth by cesarean section and central adiposity in adolescents in São Luís, Maranhão State, Brazil. This was a cohort study that included 601 participants evaluated at birth and at 18-19 years. At birth we assessed type of delivery, maternal education, family income, maternal marital status, maternal body mass index before pregnancy, prenatal care, maternal smoking habit, gestational age at delivery and intrauterine growth restriction. In the adolescents, we evaluated central adiposity using the dual X-ray energy absorptiometry method. The indicators of central fat used were the trunk-to-total fat mass ratio (T/T), the android-to-gynoid fat mass ratio (A/G), the trunk-to-limb fat mass ratio (T/Lb), and the trunk-to-leg fat mass ratio (T/Lg). A theoretical model for the study of associations was developed using directed acyclic graphs, which allowed selecting the variables that required minimum adjustment for inclusion in the predictive model of exposure to cesarean delivery. The data were analyzed with marginal structural models weighted by the inverse of the probability of selection. A total of 38.6% of the adolescents studied were delivered by cesarean section. There was no significant difference in the central adiposity of adolescents delivered by cesarean section according to the indicators used: T/T ( coefficient = -0.003; 95%CI: -0.013; 0.007), A/G (coefficient = 0.001; 95%CI: -0.015; 0.018); T/Lb (coefficient = -0.016; 95%CI: -0.048; 0.016); T/Lg (coefficient = 0.014; 95%CI: -0.060; 0.030). In conclusion, there was no association between cesarean section delivery and greater central adiposity in the studied adolescents.